Klaagliedere 3:42: vergifnis of nie-vergifnis? - O’Kennedy, D. F. (Faculty of Theology, University of the Free State, 2014)
Lamentations 3:42: forgiveness or non-forgiveness? This article investigates the short prayer of Lamentations 3:42, the only text in the prayer literature that uses the particle לא (no) together with the term סלח (forgive). The exegetical study focuses on the literal, historical and theological dimensions of the short prayer. The questions posed by this article is: Does this text portray God's unwillingness to forgive? Does Lamentations 3 only speak about punishment and judgement or do we find references to divine forgiveness? Lamentations 3 speaks about punishment, but not rejection or unwillingness to forgive. The worshipper in verse 42 confronts God with his real self: He is supposed to forgive. In the rest of chapter 3 we find reminders of God's forgiving heart: mercy and compassion (vv. 22, 32); faithfulness (v. 23); kindness (vv. 25, 26, 27); salvation (v. 26); and steadfast love (v. 32).

Hierdie artikel poog om die volgende vrae te probeer beantwoord: Getuig Klaagliedere 3:42 dat God nie wil vergewe nie? Praat hoofstuk 3 net oor straf óf is daar ook verwysings na Goddelike vergifnis? ’n Eksegetiese studie van die kort gebed word gedoen waarin eerstens die literêre- en historiese dimensie bespreek word en daarna die teologiese dimensie. Laastens word Klaagliedere 3:42 met die ander jls gedeeltes vergelyk.
Keywords: Lamentations 3:42; Forgiveness; Punishment